Prevalence of Prediabetes and the Associated Risk of Kidney Disease in Apparently Healthy Subjects in Nnewi, Anambra State, Nigeria - O.P, Ozomma; E.C, Ogbodo; R.A, Analike; I.P, Ezeugwunne; C.E, Onah; U.K, Amah; M.C, Ugwu; M.O, Obiorah; P.C, Oha; J.U, Egbe; S.C, Meludu (Journal of Diseases, 2017)
This study was designed to investigate the prevalence of prediabetes and the associated risk of kidney disease in Nnewi, Nigeria. A total of 277 apparently healthy subjects (73males and 204 females) who were willing to participate were recruited. Anthropometric indices and blood pressure were measured using standard methods while the demographic data and dietary pattern of subjects were obtained using a well-structured questionnaire. 5mls of blood was collected from eligible subjects (20 prediabetes and 20 non prediabetes ) and dispensed in fluoride oxalate and plain containers for glucose, creatinine (Cr), Urea(Ur), Na+, K+, Cl-, and HCO3- estimation respectively using standard methods. The result showed a prevalence of 7.2% prediabetes in the population. BMI was significantly higher in prediabetes than the control groups (39.4±5.8 vs 29±4.4kg/m2; P>0.05). Again, significant increases in the prediabetic values of FBG (117.54±16.84 vs 83±16.84mg/dl; P>0.05) than the control group were observed. The SBP (128± 11.26 vs 120±2.2mmHg; P>0.05) and DBP (92±4.43 vs 60±5.3mmHg; P>0.05) was also higher in prediabetic groups. Interestingly, result showed no significant difference between the renal parameters in prediabetes and non prediabetes (p>0.05). The study therefore, suggests that the major determinant for predabetes in the study population may be hypertension and obesity whereas kidney function was not impaired.